Evaluation on physical, chemical and biological properties of casts of geophagous earthworm, Metaphire tschiliensis tschiliensis - Teng, Suk Kuan; Abd Aziz, Nor Azwady; Mustafa, Muskhazli; Abd. Aziz, Suraini; Yan, Yi Wei (Academic Journals, 2012)
Earthworms are soil dwellers that have profound effects on soil ecosystem. Their feeding and burrowing activities help to incorporate soil particles with organic matter and redistribute them back into the soil via casts. The casts produced enhance microbial activities in soil that promote nutrient cycling. The present study was carried out to examine the physical, chemical and biological properties of casts produced by soil dwelling earthworm, Metaphire tschiliensis tschiliensis. Prior to inoculation of earthworms, the soil was incubated for two weeks at room temperature with moisture content of 20%. Worm worked soil and earthworm casts produced were collected for analysis after one month. Our results demonstrated that earthworm casts contained higher organic matter (9.84 ± 0.60%) and humic acid (1.33 ± 0.25%) compared to bulk soil. Total N, Ca, S, Al and Zn contents were also found to be higher in earthworm casts. Besides that, earthworm casts exhibited higher colony forming units (CFU), indicating the presence of higher microbial population. The study suggested that cast produced by M. tschiliensis tschiliensis could improve the physical and chemical properties of the soil. It also contained higher microbial population compared to soil without earthworm.